Prevalence of Sarcoptes scabiei in Patients with Suspected scabies - Yücel, Ahmet; Yılmaz, Mustafa (Galenos Publishing House, 2021)
Objective: Scabies is caused by an ectoparasite called Sarcoptes scabiei (S. scabiei), which penetrates the epidermis through skin folds and burrows in the stratum corneum, following the development of tunnels (sillion). The disease is specifically characterised by keratosis, allergy and itching that increases at night-time. This study aimed to investigate the frequency of S. scabiei in patients with a pro-diagnosis of scabies. Methods: Between January 2012 and December 2019, a total of 746 [n=388 (52%), female; n=358 (48%) male] patients aged 0-80 years were admitted to Fırat University Hospital Parasitology-mycology Laboratory. Skin scrapings were taken from suspected lesions on anatomic regions such as the hands (wrist, interdigital skin, fingertip and palm), abdomen, penis and legs (thigh and bottom foot). They were examined under a light microscope after adding 15% potassium hydroxide solution. Results: S. scabiei was positive in 139 (18.63%) of 746 patients including a mother and her daughter and a married couple, where 68 (9.11%) were female and 71 (9.52%) were male. Conclusion: To our best knowledge, this is the first comprehensive study of scabies in Elazığ. Despite the recent socio-economic and cultural developments observed in our country, scabies and all other parasitic infestations still remain to be important problems. We believe that improvement of the public vigilance together with early diagnosis will improve sanitation and provide protection against scabies and parasitic infestations. © 2021 Turkish Society for Parasitology.
Uyuz Ön Tanılı Hastalarda Sarcoptes scabiei Yaygınlığının Araştırılması
Keywords: 15% KOH; Sarcoptes scabiei; scabies; Skin scraping